Tele-rehabilitation for people with dementia in the COVID-19 pandemic: A case-study. (13th April 2021) - Lorito, C. Di; Duff, C.; Rogers, C.; Tuxworth, J.; Bell, J.; Fothergill, R.; Wilkinson, L.; Bosco, A.; Howe, L.; O'Brien, R.; Godfrey, M.; Dunlop, M.; et al.
Abstract : Introduction: The Promoting Activity, Independence and Stability in Early Dementia (PrAISED) is delivering an exercise programme for people with dementia. The Lincolnshire partnership NHS foundation Trust successfully delivered PrAISED through a video-calling platform during the COVID-19 pandemic. Objectives: This qualitative case-study identified participants that video delivery worked for, and highlighted its benefits and challenges. Methods: Interviews were conducted with participants with dementia, caregivers and therapists, and analysed through thematic analysis. Results: Video delivery worked best when participants had a supporting carer, when therapists showed enthusiasm and had an established rapport with the client. Benefits included time-efficiency of sessions, enhancing participants' motivation, caregivers' dementia awareness and therapists' creativity. Limitations included users' poor IT skills and resources. Conclusions: The COVID-19 pandemic required innovative ways of delivering rehabilitation. This study supports that people with dementia can use tele rehab, but success is reliant on having a caregiver and an enthusiastic and known therapist.